“ESTRENO” Experiencia de dirección y realización de un cortometraje alrededor de la vejez y la decadencia. - Olaya Ravenna, José Álex Moisés (2020)
This document aims to accompany the reader through the creative process behind the making of the short film “OPENING NIGHT”, going over the decisions made in each area (screenplay, direction, photography, art, sound and distribution) to tell the story of David González, an elderly actor who, seeing his career plunged into oblivion, seeks to put one last play before the senile dementia that he suffers, which is gradually taking away his faculties, forbids it. Taking into account cinematographic references such as “Damien Chazelle’s “Whiplash” and Alexander Payne’s “Nebraska”, the artistic bets that were made in order to deal with complex subjects such as fear of oblivion, decadence, passion and sacrifice will be described one by one, arriving to lessons from both the shooting and the final result, mainly from the director's perspective, having analyzed -as well- the opinions of the audience that had the opportunity to see the short film